ANALISA PENGARUH PENAMBAHAN GRAPHENE OXIDE TERHADAP SIFAT MEKANIK DAN KETAHANAN KOROSI NANOKOMPOSIT POLIMER: ANALISIS BIBLIOMETRIK - Muhammad Ashbar As-Silmy; Wahyu Ridho Pratama; Erza Arkan Zharif (JURNAL INDUSTRI DAN TEKNOLOGI SAMAWA, 2026)
This study aims to analyze the effect of graphene oxide (GO) addition on the mechanical and corrosion resistance properties of polymer nanocomposites through a bibliometric approach. Data were obtained from the Scopus, Web of Science, and Dimensions databases covering publications from 2022 to 2025. The analysis used VOSviewer and Biblioshiny to identify publication trends, keyword relationships, and thematic structures. The results show that graphene oxide is the core research theme, strongly associated with mechanical strengthening, corrosion resistance, and polymer interfacial stability. The main clusters include mechanical enhancement, surface protection, and multifunctional applications such as membranes and hydrogels. Thematic mapping indicates that graphene oxide research is shifting from experimental studies to multidisciplinary applications emphasizing functionalization optimization and high-precision characterization. Overall, this study highlights the potential of graphene oxide as an interfacial reinforcement material that enhances the performance and environmental durability of polymer nanocomposites while providing strategic direction for future multifunctional material development.